2009
DOI: 10.9775/kvfd.2011.4922
|View full text |Cite
|
Sign up to set email alerts
|

Pinanın (Pinna nobilis, Linnaeus 1758) Büyüklüğe Bağlı Olarak İzmir Körfezi Ege Denizi Türkiye de Askı Kültür Sisteminde Yetiştiriciliği

Abstract: SummaryThe growth and survival of fan mussel (Pinna nobilis, Linnaeus) juveniles, from natural spatfall, were compared in two groups (large and small size) in Karantina Island Izmir, Turkey, between December 2004 and April 2006. Total live weight, shell length, width and thickness of fan mussel were measured monthly during the study period. Small (32 mm) and large (73 mm) size groups of fan mussel individuals reached 140.25±10.46 mm and 154.36±16.12 mm in length and 64.64±17.98 g and 99.74±30.53 g in live weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…In our conditions, we recorded a long spawning period, which can be indirectly confirmed by the relatively large oscillation in the dimensions of collected juveniles with collectors, where lengths range from 18.1 to 94.3 mm, with mean values of 35.2 ± 14.3 mm, similar to the size values in previous cultivation experiments [41]. According to some authors, the planktonic phase of larvae lasts 5-10 days [49] and we can conclude that acceptance on our collectors occurred over 5-6 months because such a growth rate from the minimum to maximum size of collected individuals was confirmed in previous post-larval growth experiments [11,25]. The length of spawning and multiple spawning events can characterize the species in a particular aquatorium.…”
Section: Histological Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…In our conditions, we recorded a long spawning period, which can be indirectly confirmed by the relatively large oscillation in the dimensions of collected juveniles with collectors, where lengths range from 18.1 to 94.3 mm, with mean values of 35.2 ± 14.3 mm, similar to the size values in previous cultivation experiments [41]. According to some authors, the planktonic phase of larvae lasts 5-10 days [49] and we can conclude that acceptance on our collectors occurred over 5-6 months because such a growth rate from the minimum to maximum size of collected individuals was confirmed in previous post-larval growth experiments [11,25]. The length of spawning and multiple spawning events can characterize the species in a particular aquatorium.…”
Section: Histological Analysissupporting
confidence: 89%
“…Gametogenesis was also investigated, with findings indicating it is generally similar to other shellfish species [24]. The potential for suspension farming was explored in the eastern Mediterranean [25] alongside growth possibilities in commercial production conditions for oyster and mussel parks in the Adriatic [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other environmental parameters, such as chlorophyll-a and DO showed an indirect correlation with growth in the present study. On the contrary, Acarli et al (2011) found a positive correlation between growth and chlorophyll-a and particulate inorganic matter, and no correlation with temperature in P. nobilis. The different methods used to measure chlorophyll-a in both studies, however, impede a deeper comparison of this variable between them.…”
Section: Discussioncontrasting
confidence: 56%
“…Katsanevakis (2007) also notes low mortality in natural conditions in Lake Vougliameni, Greece (7 deaths in 160 individuals). Acarli et al (2011b) monitored the mortality of young P. nobilis in suspended PVC cages in Izmir Bay. A 7% mortality rate was recorded in a group of smaller individuals (shell lenght 32 mm).…”
Section: Resultsmentioning
confidence: 99%